Genotoxic effects of the cyanobacterial pentapeptide nodularin in HepG2 cells. (February 2019) - Štern, A.; Rotter, A.; Novak, M.; Filipič, M.; Žegura, B.
Abstract: The cyanobacterial pentapeptide nodularin (NOD), mainly produced by genus Nodularia, is a potent inhibitor of protein phosphatases PP1 and PP2A, and causes animal mortality. The few studies available indicate that NOD is a potential non-genotoxic carcinogen. In the present study we evaluated NOD (0.01, 0.1 and 1 μg/ml) genotoxic activity in human hepatoma (HepG2) cells with the comet, γH2AX and cytokinesis block micronucleus cytome assays. In addition, induction of oxidative stress was studied. Moreover changes in the expression of selected genes from the P53 pathway, involved in the response to DNA damage ( P53, GADD45α, CDKN1A, MDM2 ), apoptosis ( BAX, BCL2 ) and oxidative stress ( GPX1, GSR, GCLC, CAT, SOD1 ) were determined using qPCR. Non-cytotoxic concentrations induced time and dose dependant increase in reactive oxygen species (ROS) production and substantially increased the formation of oxidative DNA damage. In addition, elevated formation of micronuclei was detected. For the first time it has been shown that NOD deregulated the mRNA level of DNA damage ( CDKN1A, GADD45α ) and oxidative stress ( GPX1, GSR, GCLC, CAT and SOD1 ) responsive genes and anti-apoptotic gene BCL2 . Our results provide new evidence that NOD genotoxic effects are mediated through ROS production, already at low environmentally relevant concentrations. Highlights: NOD enhanced ROS formation in HepG2 cells. NOD caused oxidative DNA damage at environmentally relevant concentrations. NOD induced formation of micronuclei. NOD deregulated the expression of DNA damage and oxidative stress responsive genes. NOD deregulated the mRNA expression of antiapoptotic gene BCL2.